2014
DOI: 10.1111/avsc.12092
|View full text |Cite
|
Sign up to set email alerts
|

Response of community‐aggregated plant functional traits along grazing gradients: insights from African semi‐arid grasslands

Abstract: Questions Plant communities fulfil key functions in the ecosystem, which can be characterized by their plant functional traits. In functional ecology, plant communities are considered to hold a set of trait attributes reflecting a specific plant strategy adapted to persist in the environment to which they are exposed. In semi‐arid grasslands of the Republic of South Africa, we addressed the following questions: how are community‐aggregated plant functional traits (CPFT) shaped by grazing gradients; which plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 53 publications
6
41
0
1
Order By: Relevance
“…The negative correlation between fitted and observed forage variables (Table 4) agrees with previous observations of rangelands' decreasing forage quality with increasing biomass (Moreno García et al, 2014), and underlines the independence of both models.…”
Section: Reflectance As a Proxy Of Forage Propertiessupporting
confidence: 89%
“…The negative correlation between fitted and observed forage variables (Table 4) agrees with previous observations of rangelands' decreasing forage quality with increasing biomass (Moreno García et al, 2014), and underlines the independence of both models.…”
Section: Reflectance As a Proxy Of Forage Propertiessupporting
confidence: 89%
“…Our results support this hypothesis: Protection from heavy grazing led to a shift toward more conservative leaf traits (low SLA, low foliar N mass , and high LDMC). Other research in grasslands around the world has shown similar patterns (Cingolani et al, 2005;Louault et al, 2005;Wesuls et al, 2012;Moreno García et al, 2014). A community-level shift in ungrazed communities toward reduced acquisition and increased conservation Table 2).…”
Section: Functional Traitsmentioning
confidence: 65%
“…These species can be characterized as slow-growing perennial species that allocate a relatively small proportion of their energy to reproduction and produce litter that decomposes slowly (Reich et al, 1997;Wright et al, 2004). These findings contribute to a growing body of evidence that there are consistent shifts in community-level leaf traits under a variety of grazing regimens around the world (Louault et al, 2005;Laliberté et al, 2012;Wesuls et al, 2012;Moreno García et al, 2014). Species with low SLA are at a competitive advantage when protected from heavy grazing because they are able to reduce resource availability.…”
Section: Management Implicationsmentioning
confidence: 69%
See 1 more Smart Citation
“…Investigating complex microbial communities from a purely functional point of view provides an interesting insight because their taxonomic diversity may be very high and varying in time while, owing to environmental selection pressure, their ecosystemic functions are often ubiquitous and much more stable in time. The functional profiling of microbial communities has motivated the adaptation of concepts borrowed from environmental and plant functional ecology to the framework of microbial ecology, such as community aggregated traits [9, 10], which can be quantified through abundance computation of specific genes or predefined pathways from WGS data. These taxon-free approaches allow the study of key processes at the ecosystem level and correlate environmental factors and ecosystem functions [11].…”
Section: Introductionmentioning
confidence: 99%